The Importance of Medical Terms in English Lessons - Musaeva G. I. (Open Academia, 2023)
The article considers the tasks of studying medical terminology in English lessons. Medical terminology is represented by a macro terminal system consisting of subsystems, each of which has its own characteristics. This phenomenon should be taken into account when creating a system of tasks and exercises for teaching medical students at English lessons.
Keywords: medical terminology; English language; subsystem